Iron–Sulfur Clusters toward Stresses: Implication for Understanding and Fighting Tuberculosis - Ingie Elchennawi; Sandrine Ollagnier de Choudens (Inorganics, 2022)
Tuberculosis (TB) remains the leading cause of death due to a single pathogen, accounting for 1.5 million deaths annually on the global level. Mycobacterium tuberculosis, the causative agent of TB, is persistently exposed to stresses such as reactive oxygen species (ROS), reactive nitrogen species (RNS), acidic conditions, starvation, and hypoxic conditions, all contributing toward inhibiting bacterial proliferation and survival. Iron–sulfur (Fe-S) clusters, which are among the most ancient protein prosthetic groups, are good targets for ROS and RNS, and are susceptible to Fe starvation. Mtb holds Fe-S containing proteins involved in essential biological process for Mtb. Fe-S cluster assembly is achieved via complex protein machineries. Many organisms contain several Fe-S assembly systems, while the SUF system is the only one in some pathogens such as Mtb. The essentiality of the SUF machinery and its functionality under the stress conditions encountered by Mtb underlines how it constitutes an attractive target for the development of novel anti-TB.